Kinematics of reaching and implications for handedness in rhesus monkey infants - Nelson, Eliza L. (2011)
Kinematic studies of reaching in human infants using two-dimensional (2-D) and three-dimensional (3-D) recordings have complemented behavioral studies of infant handedness by providing additional evidence of early right asymmetries. Right hand reaches have been reported to be straighter and smoother than left hand reaches during the first year. Although reaching has been a popular measure of handedness in primates, there has been no systematic comparison of left and right hand reach kinematics. We investigated reaching in infant rhesus monkeys using the 2-D motion analysis software MaxTRAQ Lite+ (Innovision Systems). Linear mixed-effects models revealed that left hand reaches were smoother, but not straighter, than right hand reaches. An early left bias matches previous findings of a left hand preference for reaching in adult rhesus monkeys. Additional work using this kind of kinematic approach will extend our understanding of primate handedness beyond traditional studies measuring only frequency or bouts of hand use.